Long-Term Integrated Crop–Livestock–Forestry Systems Recover the Structural Quality of Ultisol Soil - Matos, Aline Marchetti Silva [UNESP]; Bonini, Carolina dos Santos Batista [UNESP]; Moreira, Bruno Rafael de Almeida [UNESP]; Andreotti, Marcelo [UNESP]; Heinrichs, Reges [UNESP]; Silva, Diogo Tiago da; Souza, José Augusto Liberato de [UNESP]; Santos, Melissa Alexandre [UNESP]; Andrighetto, Cristiana [UNESP]; Pavan, Gustavo Mateus; Barretto, Vitor Corrêa de Mattos [UNESP]; Neto, Alfredo Bonini [UNESP] (MDPI, 2022)
Integrated Crop–Livestock–Forestry Systems (ICLFS) offer stakeholders sustainable options to produce goods and services. Those additionally manifest as enablers of environmental conservation of soil functioning. We, therefore, analyzed the quality of Ultisol for physical and chemical properties under restorative or regenerative models of long-term (nine years) ICLFS. The arrangements comprised integrated Crop–Livestock; integrated Crop-Livestock-Forestry, integrated Crop–Livestock–Forestry with a single or triplicate rows of Eucalyptus; and Eucalyptus plantation, natural vegetation, and bare soil with resurgence of grasses (reference). We collected samples of soil at 0.05, 0.05–0.1, and 0.1–0.2 m depths throughout the areas to quantify standard properties, including water infiltration, hydraulic conductivity, degree of flocculation, mechanical resistance to penetration, stability of aggregates, physical fractioning of organic matter, and fertility. We applied principal component analysis to analytical data to calculate accurate discriminant variables to distinguish systems by structural quality. We obtained evidence for the crop–livestock framework improving physical and chemical properties; hence, this intervention outperformed others in developing environmental restoration. Additionally, as the reference consisted of comparable properties to those in integrative systems and native vegetation, it supported the ability of the soil to gradually recover itself over time. Therefore, our study provides knowledge to advance the field’s prominence in implementing ICLFS for the environmental reclamation of the condition or process degrading the soil and its functions for sustainable agricultural production.
Keywords: environmental restoration; Eucalyptus; pasture; soil degradation; sustainable production